Production trends and export performance analysis of Indian fresh mangoes and mango pulp: A two-decade assessment (2004-2024) - Nixon Tony , A; Divya, K; Bini Sundar, S T; Uma, K; Parimalarangan, R (Plant Science Today, 2025)
India is the largest producer and consumer of mangoes, accounting for approximately 45 % of the world’s production. Mangoes and mango pulp export holds a significant position in Indian agricultural trade. The secondary data obtained from Indiastat and Agricultural and Processed Food Products Export Development Authority (APEDA) were examined using Compound Annual Growth Rate (CAGR), instability indices and the Markov chain to assess production performance, instability in production and exporting countries and trade directions. The analysis demonstrates an in-depth analysis of production trends & performance and export directions of mangoes and mango pulp over the last two decades, as they significantly contribute to export. The findings revealed an overall increase in the area, production and productivity of mango with low instability, indicating low fluctuations. The UAE exhibited low instability with 29.5 % of fresh mango export, whereas Saudi Arabia (20.5 %) and the USA (17.4 %) showed low instability in mango pulp export. The UAE remains the stable importers of fresh mangoes with 66 % retention potential, while Saudi Arabia and UAE were the stable importers of mango pulp with the retention potential about 97 % and 67 % respectively. The forecasted export up to 2028-29 revealed that the UAE and UK continued to be the promising markets of Indian mangoes, while Saudi Arabia and USA for Indian mango pulp. The study emphasizes the significance of improving trade infrastructure, raising quality standards and promoting policy support to boost India's export competitiveness for mango and mango pulp in the global market.